Privacy, new technology and constitutional adjudication in the light of Antonin Scalia’s originalist interpretation - Bernaczyk, Michał; Frąckowiak, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The article offers a brief outline of the United States Supreme Court Justice Antonin Scalia's originalist method of constitutional interpretation which became a significant part of legal discourse among American scholars and echoed even in Polish public life. The text focuses on two famous privacy decisions issued by The U.S. Supreme Court involving the unwarranted search and seizure of private premises via non-physically intrusive techniques. The authors try to shed more light on a dillema whether originalist approach to constitutional interpretation may still be suitable to 21st Century challenges offered to consitutional law by proliferation of new surveillance techniques.
Keywords: rule of law; United States Supreme Court; fourth amendment; Privacy Shield; new technology; Supreme Court Justices visiting Poland; originalism; search and seizure; right to privacy; surveillance; constitutional interpretation; textualism; The Living Constitution doctrine; European Court of Human Rights